A Ph-Responsive Nanoparticle Targets the Neurokinin 1 Receptor in Endosomes to Prevent Chronic Pain - Constandil-Cordova, L; Pelissier, T (Nature Research, 2019)
Nanoparticle-mediated drug delivery is especially useful for targets within endosomes because of the endosomal transport mechanisms of many nanomedicines within cells. Here, we report the design of a pH-responsive, soft polymeric nanoparticle for the targeting of acidified endosomes to precisely inhibit endosomal signalling events leading to chronic pain. In chronic pain, the substance P (SP) neurokinin 1 receptor (NK1R) redistributes from the plasma membrane to acidified endosomes, where it signals to maintain pain. Therefore, the NK1R in endosomes provides an important target for pain relief. The pH-responsive nanoparticles enter cells by clathrin- and dynamin-dependent endocytosis and accumulate in NK1R-containing endosomes. Following intrathecal injection into rodents, the nanoparticles, containing the FDA-approved NK1R antagonist aprepitant, inhibit SP-induced activation of spinal neurons and thus prevent pain transmission. Treatment with the nanoparticles leads to complete and persistent relief from nociceptive, inflammatory and neuropathic nociception and offers a much-needed non-opioid treatment option for chronic pain. © 2019, The Author(s), under exclusive licence to Springer Nature Limited.